Proteogenomic Tools in the Assessment of Pharmacological Effects of Natural Compounds - Radu Albulescu; Adrian Albulescu; Georgeta Caraene; Corina Bubueanu; Alice Grigore; Maria Petrescu; Roxana-Mădălina Stoica (Chemistry Proceedings)
Proteogenomics is a recently developed omics application, adding enhancing the sensitivity of proteomics, and thus making possible the detection of proteome markers in very tiny amounts of samples. Even if the filed developed only in the last 10 years, the technology is very intensely applied in clinical diagnostics, and more recently, efforts are made to use it in non-clinical, in vitro and in vivo studies. The aim of this study was to investigate the applicability of single-plex and multiplex assays in the evaluation of proteome changes generated in vitro by the exposure to several standard compounds. The extracts demonstrated weak cytotoxic effects. The detection of cytokines Performing the same assays on tissue lysates permitted only the detection of low levels of cytokines.